Implementasi UU No. 35 Tahun 2014 tentang Perlindungan Anak terhadap Kasus Pernikahan Dini di Kecamatan Watubangga - Iis fahrizah ulfah; Aris Nur Qadar Ar-Razak (Institut Agama Islam (IAIN) Kendari, 2025)
This study aims to analyze the implementation of Law No. 35 of 2014 on Child Protection in Watubangga Subdistrict, Kolaka Regency, as well as the challenges faced in its implementation. Data collection was carried out through interviews and direct observation in the field. Based on the research findings, the local government has implemented a number of strict mechanisms to prevent early marriage. These mechanisms include recommendations from the Women's Empowerment and Child Protection Agency (DP3A) and the Health Agency, as well as guidance for prospective couples who wish to marry. The Religious Court also plays an important role in providing legal education to the community about the dangers of early marriage. In general, the implementation of this law has made a real contribution to reducing the rate of early marriage and improving the protection of children's rights in the region. However, the implementation of this law still faces a number of challenges. The main challenge is the high rate of early marriage caused by out-of-wedlock pregnancies. This situation creates a dilemma between strict law enforcement and social pressure from the community. Additionally, the low level of public awareness about the importance of child protection further complicates efforts to implement this law. Therefore, a more holistic approach is needed, involving various parties, including the government, the community, and relevant institutions. More intensive education and outreach at the community level, along with cross-sectoral support, are key to enhancing the effectiveness of child protection and preventing early marriage more effectively. Keywords: Implementation; Child Protection; Early Marriage.